A first, naturally occurring substitution at the second pyrethroid receptor of voltage‐gated sodium channel of Aedes aegypti - Itokawa, Kentaro; Furutani, Shogo; Takaoka, Aki; Maekawa, Yoshihide; Sawabe, Kyoko; Komagata, Osamu; Tomita, Takashi; Lima Filho, José Luiz; Alves, Luiz Carlos; Kasai, Shinji (Pest Management Science, 2021)
BACKGROUND Aedes aegypti is a remarkably effective mosquito vector of epidemiologically important arboviral diseases including dengue fever, yellow fever and Zika. The present spread of resistance against pyrethroids, the primary insecticides used for mosquito control, in global populations of this species is of great concern. The voltage‐gated sodium channel (VGSC) in the nervous system is the known target site of pyrethroids in insects. Past studies have revealed several amino‐acid substitutions in this channel that confer pyrethroid resistance, which are known as knockdown resistance (kdr) mutations. RESULTS This study investigated a laboratory colony of Ae. aegypti, MCNaeg, established from larvae collected in Rio de Janeiro, Brazil in 2016. The MCNaeg colony showed strong resistance against pyrethroids without laboratory selection. Of the two VGSC gene haplotypes present within this colony, one harbored three known kdr mutations, V410L, V1016I, and F1534C, and the other harbored only the known F1534C mutation. In latter haplotype, we also found novel amino‐acid substations including V253F. Previous molecular modeling and electrophysiological studies suggest that this residue serves a pyrethroid‐sensing site in the second receptor, PyR2. Our genetical analysis showed that the haplotype harboring V253F and F1534C is associated with equal or slightly stronger resistance than the other triple kdr haplotype to both Type I and Type II pyrethroids. CONCLUSION The novel substitution V253F is potentially involved in pyrethroid resistance in Ae. aegypti. Further studies are needed to elucidate the role of this substitution in the pyrethroid susceptibility of VGSC. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. We found a novel amino‐acid substitution V253F in the voltage‐gated sodium channel in Aedes aegypti which is potentially involved in pyrethroid resistance of this vector mosquito